Работы на поселении Лобойковка 1 в 2008 г. - Ромашко, В.А.; Тесленко, Д.Л. (Археологічні дослідження в Україні, 2009)
The results of the archaeological prospecting conducted in 2008 at the Loboykivka 1 settlement on the left bank of the Dnipro River are published here. The research at the western part of the site allowed the authors to determine three cultural and chronological horizons with the materials of the Copper Age, Berezhnivsko-Mayivska Zrubna and Zrubna-Bilozerska cultures.